Relación entre los factores sociodemográficos y académicos, el estilo cognoscitivo y el sistema de valores, con el rendimiento académico en alumnos de la facultad de psicología de la Universidad Católica de Colombia (1999)
The objective of this research was to relate socio-demographic factors, cognitive style and value system to the academic performance of Psychology students at the Católica University of Colombia, in the second term of 1997.The design used was a descrip¬tive-correlational with a sample of 196 students in representation of the whole popu¬lation of the Psychology department. The data collection instruments used were a socio demographic data survey, the Values System Test by Gordon, and the Cognitive Style Test validated by Hederich.The data base was conducted with the aid of the EXCEL program and the statistical analysis with the aid of the SPSS (Windows) statistics program.The results show that State test scores and interpersonal conformity values may predict the academic performance of students. It was also found an important asociation between high cognitive style and academic performance of students.